Perioperative Management of An Elderly with Coronary Artery Disease and Aortic Stenosis Undergoing Emergency ORIF for Intertrochanteric Fracture. Report of A Rare Case and Systematic Mini Review - Vishnu Datt; Sakshi Dhingra; Diksha Datt; Shreya Khatri; Simran Yadav; Sansar Sharma; Priyanka Dahiya; Priyanka Kaushik; Rahul Singla; Bharti Yadav; KS Goel (International Journal of Health Sciences and Research, 2026)
1. Rapp AH, Hillis LD, Lange RA, et al. Prevalence of coronary artery disease in patients with aortic stenosis with and without angina pectoris, Am J Cardiol, 2001, vol. 87 (pg. 1216-1217) 2. Toufik Abdul-Rahman a, Ileana Lizano Jubert b, Neil Garg c, et al. The common pathobiology between coronary artery disease and calcific aortic stenosis: Evidence and clinical implications. Progress in Cardiovascular Diseases Volume 79, July–August 2023, Pages 89-99 3. Li Z, Anderson I, Amsterdam EA, et al. Effect of coronary artery disease extent on contemporary outcomes of combined aortic valve replacement and coronary artery bypass graft surgery. Ann Thorac Surg. 2013;96:2075–2082. doi: 10.1016/j.athoracsur.2013.07.035. 4. Jean-Michel Paradis, Justin Fried, Tamim Nazif,et al. Aortic stenosis and coronary artery disease: What do we know? What don't we know? A comprehensive review of the literature with proposed treatment algorithms, European Heart Journal, Volume 35, Issue 31, 14 August 2014, Pages 2069–2082, https://doi.org/10.1093/eurheartj/ehu247 5. Tomohiko Taniguchi, MD, Takeshi Morimoto, MD,MPH, Hiroki Shiomi, MD,et al. Sudden Death in Patients With Severe Aortic Stenosis: Observations From the CURRENT AS Registry Journal of the American Heart Association. Volume 7, Number 11 https://doi.org/10.1161/JAHA.117.008 6. Minamino-Muta, E., Kato, T, Morimoto, T. et al. Causes of Death in Patients with Severe Aortic Stenosis: An Observational study. Sci Rep 7, 14723 (2017). https://doi.org/10.1038/s41598-017-15316-6 7. Minjung Bak, MD, Seung‐Hwa Lee, MD, Sung‐Ji Park, MD, PhD, et al. Perioperative Risk of Noncardiac Surgery in Patients With Asymptomatic Significant Aortic Stenosis: [A 10‐Year Retrospective Study.Journal of the American Heart Association,Volume 13, Number 9 https://doi.org/10.1161/JAHA.123.032675. 8. Agarwal S, Rajamanickam A, Bajaj NS, et al. Impact of aortic stenosis on postoperative outcomes after noncardiac surgeries. Circ Cardiovasc Qual Outcomes. 2013;6:193–200. 9. Pibarot P, Dumesnil JG. Improving assessment of aortic stenosis. J Am Coll Cardiol. 2012;60:169–80. doi: 10.1016/j.jacc.2011.11.078. 10. Stewart BF, Siscovick D, Lind BK. et al. Clinical factors associated with calcific aortic valve disease. Cardiovascular Health Study. J Am Coll Cardiol. 1997;29:630–4. doi: 10.1016/S0735-1097(96)00563-3. 11. Harish Ramakrishna, MD, FASE, FACC | Ryan C. Craner, MD | Patrick A. Devaleria, MD. et al.Valvular Heart Disease: Replacement and Repair. In KAPLAN’S Cardiac Anesthesia for Cardiac And Non cardiac Surgery. Editor. editor, Joel A. Kaplan; associate editors, John G.T. Augoustides, Gerard R. Manecke, Jr., Timothy Maus, David L.Reich.. 7th Edition. Philadelphia, PA : Elsevier, [2017],pp 770-817. 12. Joseph J, Naqvi SY, Giri J, et al. Aortic Stenosis: Pathophysiology, Diagnosis, and Therapy. The American Journal of Medicine, vol 130, issue 3,253- 263, 2017 13. Vick G.W. 3rd, The Gold Standard for Noninvasive Imaging in Coronary Heart Disease: Magnetic Resonance Imaging. Curr. Opin. Cardiol. 2009;24:567. doi: 10.1097/HCO.0b013e3283315553. 14. Mark DB, Berman DS, Budoff MJ, et al. ACCF/ACR/AHA/NASCI/SAIP/SCAI/SCCT 2010 expert consensus document on coronary computed tomographic angiography: a report of the American College of Cardiology Foundation Task Force on Expert Consensus Documents. J Am Coll Cardiol. (2010) 55(23):2663–99. doi: 10.1016/j.jacc.2009.11.013 15. Opolski MP, Kim WK, Liebetrau C, et al. Diagnostic accuracy of computed tomography angiography for the detection of coronary artery disease in patients referred for transcatheter aortic valve implantation. Clin Res Cardiol. (2015) 104(6):471–80. doi: 10.1007/s00392-014-0806-z. 16. Connolly HM, Oh JK, Schaff HV, et al. Severe aortic stenosis with low transvalvular gradient and severe left ventricular dysfunction. Result of aortic valve replacement in 52 patients. Circulation. 2000;101(16):1940–1946. doi: 10.1161/01.cir.101.16.1940. 17. David Messika-Zeitoun,FESC, Dr. Guy Lloyd. Aortic valve stenosis: evaluation and management of patients with discordant grading. ESC. Vol. 15, N° 26 - 10 Jan 2018. 18. Ribouilloy C, Lévy F, Rusinaru D.et al. Outcome after aortic valve replacement for low-flow/low-gradient aortic stenosis without contractile reserve on dobutamine stress echocardiography. J Am Coll Cardiol. 2009;53(20):1865–1873. doi: 10.1016/j.jacc.2009.02.026. 19. Rosa VE, Accorsi TA, Fernandes JR,et al. Low-Flow Aortic Stenosis and Reduced Ejection Fraction: New Insights. Arq Bras Cardiol. 2015 Jul;105(1):82-5. doi: 10.5935/abc.20150080. 20. Dahl JS,Eleid MF,Michelena HI, et al. Effect of left ventricular ejection fraction on postoperative outcome in patients with severe aortic stenosis undergoing aortic valve replacement. Circ Cardiovasc Imaging. 2015;8:0. doi: 10.1161/CIRCIMAGING.114.002917 21. Ira S. Cohen. (2015), Aortic Stenosis. In A. C. Perrino Jr. & S. T. Reeves (Eds.), A practical approach to transesophageal echocardiography (3rd ed., pp. 240–257). Lippincott Williams & Wilkins. 22. Herrera RA, Smith MM, Mauermann WJ, et al. Perioperative management of aortic stenosis in patients undergoing non-cardiac surgery. Front Cardiovasc Med. 2023 Apr 6;10:1145290. doi: 10.3389/fcvm.2023.1145290. 23. Otto C.M., Nishimura R.A., Bonow R.O., et al. 2020 ACC/AHA guideline for the management of patients with valvular heart disease: a report of the American College of Cardiology/American Heart Association Joint Committee on Clinical Practice Guidelines. J Am Coll Cardiol. 2021;77:e25-e197 24. Tashiro T, Pislaru S.V, Blustin J.M. et al. Perioperative risk of major non-cardiac surgery in patients with severe aortic stenosis: a reappraisal in contemporary practice. Eur Heart J. 2014;35:2372-2381. 25. Luis S.A., Dohaei A., Chandrashekar P., et al. Impact of aortic valve replacement for severe aortic stenosis on perioperative outcomes following major noncardiac surgery. Mayo Clin Proc. 2020;95:727-737 26. Taniguchi T., Morimoto T., Shiomi H., et al. Elective non-cardiac surgery in patients with severe aortic stenosis: observations from the CURRENT AS Registry. Circ J. 2020;84:1173-1182. 27. Lerman BJ, Popat RA, Assimes TL, et al. Association of left ventricular ejection fraction and symptoms with mortality after elective noncardiac surgery among patients with heart failure. JAMA. 2019;321: 572-579] 28. Daijiro Tomii, MD, Thomas Pilgrim, MD, MSc, Michael A. Borger, MD,PhD. et al. . Aortic Stenosis and Coronary Artery Disease: Decision-Making Between Surgical and Transcatheter Management. Circulation. 2024;150:2046–2069. DOI: 10.1161/CIRCULATIONAHA.124.070502. 29. Clift CL, Goudot G, Bogut G et al. Short- and Long-Term Effects of Pulsed Ultrasound Cavitation Therapy of Calcified Valvular Interstitial Cells in Culture, Ultrasound in Medicine & Biology, 51, 11, (1936-1944), (2025). https://doi.org/10.1016/j.ultrasmedbio.2025.06.026 30. Vahanian A., Beyersdorf F., Praz F., et al. 2021 ESC/EACTS guidelines for the management of valvular heart disease. Eur Heart J. 2021;43(7):561–632. doi: 10.1093/eurheartj/ehab395. 31. Tzemos N, Therrien J, Yip J,et al. Outcomes in Adults With Bicuspid Aortic Valves. JAMA: The Journal of the American Medical Association. 2008; 300:1317–1325. doi: 10.1001/jama.300.11.1317. 32. Thompson A, Fleischmann KE, Smilowitz NR,et al. 2024 AHA/ACC/ACS/ ASNC/HRS/SCA/SCCT/SCMR/SVM guideline for perioperative cardiovascular management for noncardiac surgery: a report of the American College of Cardiology/ American Heart Association Joint Committee on Clinical Practice Guidelines. Circulation. 2024;150:e00–e00. doi: 10.1161/CIR.0000000000001285 33. Heidenreich PA, Bozkurt B, Aguilar D, et al. 2022 AHA/ACC/HFSA guideline for the management of heart failure: a report of the American College of Cardiology/American Heart Association Joint Committee on Clinical Practice Guidelines. Circulation. 2022;145:e895–e1032. 34. Ruetzler K, Smilowitz NR, Berger JS, et al. Diagnosis and management of patients with myocardial injury after noncardiac surgery: a scientific statement from the American Heart Association. Circulation. 2021;144:e287–e305. 35. Beach JM, Mihaljevic T, Svensson LG,et al. Coronary artery disease and outcomes of aortic valve replacement for severe aortic stenosis. J Am Coll Cardiol. (2013) 61(8):837–48. doi: 10.1016/j.jacc.2012.10.049 36. Thalji NM, Suri RM, Daly RC, et al. The prognostic impact of concomitant coronary artery bypass grafting during aortic valve surgery: implications for revascularization in the transcatheter era. J Thorac Cardiovasc Surg. (2015) 149(2):451–60. doi: 10.1016/j.jtcvs.2014.08.073 37. Ramee S, Anwaruddin S, Kumar G et al. The rationale for performance of coronary angiography and stenting before transcatheter aortic valve replacement: from the Interventional Section Leadership Council of the American College of Cardiology. JACC Cardiovasc Interv. 2016;9:2371–5. doi: 10.1016/j.jcin.2016.09.024 38. Zhou Y, Liu L, Cheng T, et al. Grade 3 echocardiographic diastolic dysfunction is associated with increased risk of major adverse cardiovascular events after surgery: a retrospective cohort study. Anesth Analg. 2019;129:651–658. 39. Cho DH, Park SM, Kim MN, et al. Presence of preoperative diastolic dysfunction predicts postoperative pulmonary edema and cardiovascular complications in patients undergoing noncardiac surgery. Echocardiography. 2014;31:42–49. 40. Fayad A, Ansari MT, Yang H, et al. Perioperative diastolic dysfunction in patients undergoing noncardiac surgery is an independent risk factor for cardiovascular events: a systematic review and meta-analysis. Anesthesiology. 2016;125:72–91. 41. Healy KO, Waksmonski CA, Altman RK, et al. Perioperative outcome and long-term mortality for heart failure patients undergoing intermediate- and high-risk noncardiac surgery: impact of left ventricular ejection fraction. Congest Heart Fail. 2010;16:45–49. 42. Halperin JL, Levine GN, Al-Khatib SM, et al. Further evolution of the ACC/AHA clinical practice guideline recommendation classification system: a report of the American College of Cardiology/American Heart Association Task Force on Clinical Practice Guidelines. Circulation. 2016;133:1426–1428. 43. Arnett DK, Goodman RA, Halperin JL, et al. AHA/ACC/HHS strategies to enhance application of clinical practice guidelines in patients with cardiovascular disease and comorbid conditions: from the American Heart Association, American College of Cardiology, and US Department of Health and Human Services. Circulation. 2014;130:1662–1667 44. Terré JA, Torrado J, George I,et al. Aortic Stenosis Management in Patients With Acute Hip Fracture. JACC Adv. 2024 Apr 3;3(5):100912. doi: 10.1016/j.jacadv.2024.100912 45. Yamamoto M., Kagase A., Shimura T., et al. Percutaneous aortic valve intervention in patients scheduled for noncardiac surgery: a Japanese multicenter study. Cardiovasc Revasc Med. 2020; 21:621-628. 46. London MJ, Schwartz GG, Hur K,et al. Association of perioperative statin use with mortality and morbidity after major noncardiac surgery. JAMA Intern Med 2017;177:231–242. 47. O'Brien B, Burrage PS, Ngai JY,et al. Society of Cardiovascular Anesthesiologists/European Association of Cardiothoracic Anaesthetists Practice Advisory for the management of perioperative atrial fibrillation in patients undergoing cardiac surgery. J Cardiothorac Vasc Anesth 2019; 33:12–26 48. Mets B. To stop or not? Anesth Analg. 2015 Jun;120(6):1413-9. doi: 10.1213/ANE.0000000000000758. 49. Legrand M. Should renin-angiotensin system inhibitors be held prior to major surgery? Br J Anaesth. 2024 May;132(5):831-834. doi: 10.1016/j.bja.2024.03.003. 50. Ackland GL, Patel A, Abbott TEF,et al. Stopping Perioperative ACE-inhibitors or angiotensin-II receptor blockers (SPACE) trial investigators. Discontinuation vs. continuation of renin-angiotensin system inhibition before non-cardiac surgery: the SPACE trial. Eur Heart J. 2024 Apr 1;45(13):1146-1155. doi: 10.1093/eurheartj/ehad716. 51. Hoefer D, Jonetzko P, Hoermann C, et al. Successful administration of levosimendan in a patient with low-gradient low-output aortic stenosis. Wien Klin Wochenschr. 2006; 118(1-2): 60–62, doi: 10.1007/s00508-005-0508-2. 52. Reiterer, C., Kabon, B., Taschner, A. et al. Levosimendan for postoperative subclinical heart failure after noncardiac surgery: a randomized, double-blinded, phase III trial. Nat Commun 16, 5847 (2025). https://doi.org/10.1038/s41467-025-60601-y 53. Katsaragakis S, Kapralou A, Markogiannakis H,et al.Preoperative levosimendan in heart failure patients undergoing noncardiac surgery. Neth J Med. 2008 Apr;66(4):154-9. PMID: 18424862. 54. Fakher M, Aboelghet M, Moharam A,et al. The Role of Perioperative Levosimendan in Patients with Reduced Ejection Fraction undergoing Cardiac surgery in Reducing Post-operative Hemodynamic Support. Open Access Maced J Med Sci [Internet]. 2022 May 15 ;10(B):1302-7. Doi: https://oamjms.eu/index.php/mjms/article/view/8898. 55. Negi SL, Chakorvarthy L, Gowda N,et al. Role of transesophageal echocardiography in early detection of myocardial ischemia before electrocardiography changes post arterial switch operation. Ann Card Anaesth. 2023 Oct-Dec;26(4):451-453. doi: 10.4103/aca.aca_161_22. 56. Aysen Degerli, Morteza Zabihi, Serkan Kiranyaz,et al. Early Detection of Myocardial Infarction inLow-Quality Echocardiography February 2021. IEEE Access PP(99):1-1. DOI: 10.1109/ACCESS.2021.3059595. 57. Playford D, Stewart S, Harris SA, Chan YK, Strange G. Pattern and Prognostic Impact of Regional Wall Motion Abnormalities in 255 697 Men and 236 641 Women Investigated with Echocardiography. J Am Heart Assoc. 2023 Nov 21;12(22):e031243. doi: 10.1161/JAHA.123.031243. 58. Liu JP, Pan ZB, Zhu M, Zhu GW, Song DB, Chen XZ, Qian XW. Determination of the 90% Effective Dose of Phenylephrine Boluses to Treat Spinal Anesthesia-Induced Hypotension in Patients with Severe Preeclampsia during Cesarean Delivery: A Pilot Study. Drug Des Devel Ther. 2021 Sep 7;15:3765-3772. doi: 10.2147/DDDT.S323715. 59. S. Hiruthick and K. V. L. Sanjana (2021) “Clinical Comparative Study of Effect of Two Different Doses of Phenylephrine on Spinal Induced Hypotension during Cesarean Section”, Journal of Pharmaceutical Research International, 33(47B), pp. 482–489. doi: 10.9734/jpri/2021/v33i47B33147. 60. Wenyuan Lyu , Zheng Zhang , Chengwei Li, et al. Intravenous initial bolus during prophylactic norepinephrine infusion to prevent spinal hypotension for cesarean delivery: A randomized controlled, dose-finding trial. Journal of Clinical Anesthesia. Volume 97, October 2024, 111562. 61. Khatoon K, Kocarev M, Fernando R. et al. Optimal infusion rate of norepinephrine infusion for prevention of spinal hypotension for cesarean delivery: a randomized Controlled trial, using up-down sequential allocation. Anesth Analg. 2025; 141:17–25.